Preparation method of modified zinc negative electrode and aqueous zinc ion battery
Through the combined application of laser patterning and plasma treatment, the surface texture and interface chemistry of zinc negative electrode are optimized, and the problems of zinc dendrites growth and interface side reactions are solved, and the circulation performance and coulomb efficiency of the battery are improved.
Patent Information
- Application Number
- CN202510194789.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-21
AI Technical Summary
Interface stability issues of zinc negative electrode materials in aqueous zinc ion batteries, including zinc dendrites growth and zinc negative electrode-electrolyte interface side reactions, resulting in internal short circuits of the battery, capacity attenuation and low Coulomb efficiency.
The surface of the zinc foil is patterned using ultraviolet picosecond pulse laser to form nanoscale grooves and protrusions. The surface of the zinc negative electrode is then treated by plasma technology to form an interface electric double layer structure, and the surface texture and interface chemical properties of the zinc negative electrode are optimized.
It significantly reduces the growth and side reaction of zinc dendrites, improves the electrochemical performance of zinc negative electrodes, the circulation performance and Coulomb efficiency of aqueous zinc ion batteries.
Smart Images

Figure CN119695089A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of aqueous zinc ion batteries, and in particular to a method for preparing a modified zinc negative electrode and an aqueous zinc ion battery. Background Art
[0002] In the context of the global energy structure transitioning to a low-carbon one, the development of new energy storage technologies has become a key support for achieving the "dual carbon" strategic goal. Aqueous zinc-ion batteries are considered to be a large-scale energy storage solution with great development potential due to their intrinsic safety, environmental friendliness and cost advantages. Thanks to the abundant natural reserves of metallic zinc (crust abundance of 75 ppm), high theoretical specific capacity (820 mAh / g) and low redox potential (-0.76 V relative to the standard hydrogen electrode), metallic zinc, as the active material of the negative electrode of aqueous zinc-ion batteries, has shown significant application value.
[0003] However, the core bottleneck restricting the large-scale application of aqueous zinc-ion batteries lies in the interfacial stability of zinc negative electrode materials, which is specifically manifested in the following two dimensions: First, the surface integrity defects of commercial rolled zinc foil significantly affect the electrochemical performance. The industrial rolling process leads to the widespread presence of process defects such as microcracks, mechanical scratches and unpolished edges on the surface of zinc electrodes. These micro-nanoscale structures act as high-curvature active sites, which will cause uneven distribution of zinc ion flux, accelerate dendrite nucleation and growth, and ultimately lead to internal short circuits and capacity decay in the battery.
[0004] Secondly, the lack of dynamic wettability of the solid-liquid interface exacerbates side reactions. The contact angle between the traditional zinc electrode and the electrolyte is large (usually > 90°). This non-wetting characteristic of the interface will lead to three chain effects: 1) significantly reduce the effective electrochemical active area, causing electrode passivation; 2) promote the decomposition of H2O molecules at the interface, aggravating the hydrogen evolution corrosion reaction; 3) induce local electric field distortion, forming a self-catalytic microenvironment for dendrite growth. Research data show that the above interface failure mechanism can reduce the battery Coulomb efficiency to below 85% after 50 cycles.
[0005] It is worth noting that there is a strong coupling relationship between zinc deposition morphology and interface characteristics. Disordered dendrite growth not only causes loss of active materials, but also the accumulation of "dead zinc" caused by it will lead to electrode volume expansion, forming a vicious cycle. Therefore, constructing a stable zinc deposition / dissolution interface microenvironment has become a key scientific issue in promoting the practical application of aqueous zinc-ion batteries. It is urgent to achieve the coordinated optimization of zinc foil surface morphology regulation and interface chemical modification through surface engineering strategies.
[0006] At present, in order to solve the problem of dendrite growth of zinc negative electrode, the common treatment methods are mainly the following: (1) Surface functional coating technology; regulating the zinc ion deposition dynamics by constructing an interface modification layer. In the article "An extended substrate screening strategy enabling a low lattice mismatch for highly reversible zinc anodes" published by Zhou Guangmin's team from Tsinghua University in Nat. Commun. (Nature Communications 15, Article number: 753 (2024)), a layered vermiculite coating was used to optimize the electrolyte contact angle from 95° to 27°, and the confinement effect of two-dimensional nanochannels was used to achieve directional transport of zinc ions. Lin et al. from Xichuan Normal University published an article " In-situ grown hydrophilic-zinophilic ZnCr2O4protective layer to guide horizontal Zn 2+ In the paper "deposition for dendrite-free Zn anodes for aqueous Zn-ion batteries", a dual-functional ZnCr2O4 interfacial layer was developed to reduce the wetting angle to 6.05°. + The adsorption energy (-3.12 eV) leads to dense deposition. However, the technology in this article has intrinsic defects: 1) physical / chemical deposition methods are difficult to achieve submicron thickness uniformity; 2) the Young's modulus mismatch between the coating and the substrate (>5 GPa) leads to interface delamination under cyclic stress; 3) the coating components dissolve during the formation of dynamic SEI (such as Cr³ +The dissolution rate reaches 1.8μg / cm² / cycle), which is easy to cause secondary dendrite nucleation. (2) Three-dimensional structural engineering strategy: By designing a special zinc negative electrode structure, such as a three-dimensional porous structure, the contact area is increased to achieve sufficient contact between the electrode and the electrolyte, thereby improving the transmission and deposition of zinc ions. However, this method usually has a complex preparation process, high cost, and is difficult to mass produce. The Chinese patent with publication number CN117317118A discloses a scheme of using a 1064 nm nanosecond laser to achieve B / C / N ternary co-penetration of Zn foil and construct a gradient doping layer, but the laser thermal effect (peak temperature > 1600 K) induces microcracks and ZnO phase transition, making it difficult to produce homogenously. The Chinese patent with publication number CN115360317A discloses a scheme of using a laser with a wavelength of 1064 nm to perform laser engraving to optimize the contact angle between the negative electrode surface of an aqueous zinc ion battery and the electrolyte. The positive electrode current collector is titanium foil and the positive electrode active material is V2O5. Similarly, although the use of 1064nm red light can pattern and uniformly reconstruct the interface, the thermal effect of the thermal light source will change the chemical properties of the zinc metal surface, which may cause excessive ablation and destroy the structural integrity and stability of the negative electrode. In general, although the existing zinc negative electrode treatment methods have improved the electrochemical performance of the zinc negative electrode to a certain extent, there are still many shortcomings. The modification method only delays rather than blocks dendrite nucleation, fails to reconstruct the interface double layer structure and eliminate local electric field distortion, and cannot fundamentally solve the problems of dendrite growth, low Coulomb efficiency, and poor cycle performance.
[0007] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0008] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a method for preparing a modified zinc negative electrode and an aqueous zinc ion battery, which reduces the growth of zinc dendrites on the surface of the modified zinc negative electrode and the occurrence of side reactions at the zinc negative electrode-electrolyte interface during use by combining laser patterning treatment and plasma treatment.
[0009] According to one aspect of the present disclosure, a method for preparing a modified zinc negative electrode is provided, comprising the following steps: S10, patterning the surface of the zinc foil using an ultraviolet picosecond pulse laser to obtain a laser-reconstructed zinc negative electrode; S20, using plasma technology to perform plasma treatment on the surface of the laser reconstructed zinc negative electrode to obtain a modified zinc negative electrode.
[0010] In an exemplary embodiment of the present disclosure, in step S10, the patterning process is to use a laser to directly write on the surface of the zinc foil; The processing speed of the laser direct writing is 1000-2000 mm / s, the straight line filling spacing is 0.005 mm-0.01 mm, the straight line filling angle is 0-90°, and the straight line filling times is 1-10 times.
[0011] In an exemplary embodiment of the present disclosure, the processing speed of the laser direct writing is 1200-1600 mm / s, the straight line filling spacing is 0.005 mm-0.007 mm, the filling angle is 30-60°, and the number of filling times is 2-4 times.
[0012] In an exemplary embodiment of the present disclosure, the wavelength of the laser is 355 nm; The actual power used by the laser is 1-5W, and the maximum average power of the laser is 10-30W.
[0013] In an exemplary embodiment of the present disclosure, in the laser direct writing, the angle between the laser head of the laser and the surface of the zinc foil is 90°.
[0014] In an exemplary embodiment of the present disclosure, the pattern obtained by the patterning process is a stripe pattern or a dot matrix pattern.
[0015] In an exemplary embodiment of the present disclosure, in step S20, the working gas used in the plasma treatment is at least one of helium, argon, oxygen, nitrogen, hydrogen, carbon dioxide, chlorine, xenon, and water vapor.
[0016] In an exemplary embodiment of the present disclosure, the gas purity of the working gas is greater than or equal to 99.99%.
[0017] In an exemplary embodiment of the present disclosure, in step S20, the plasma treatment process includes: The first stage: the gas flow rate is in the range of 10-80sccm, the gas vacuum is in the range of 10Pa-30Pa, the RF power is in the range of 50W-200W, and the processing time is ≥100s; The second stage: the gas flow rate is in the range of 80 to 200 sccm, the gas vacuum is in the range of 30 Pa to 50 Pa, the RF power is in the range of 200 W to 300 W, and the processing time is ≥100 s.
[0018] According to another aspect of the present disclosure, an aqueous zinc ion battery is provided, wherein the negative electrode of the aqueous zinc ion battery adopts the modified zinc negative electrode prepared by the above preparation method.
[0019] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.
[0021] Figure 1 The present invention is a flow chart of a method for preparing a modified zinc negative electrode in one embodiment of the present invention.
[0022] Figure 2 In one embodiment of the present invention, optical microscope characterization comparison diagrams before and after the laser patterning treatment of the surface of the zinc foil are provided; wherein (a) is an optical microscope characterization diagram before the laser patterning treatment of the surface of the zinc foil, and (b) is an optical microscope characterization diagram after the laser patterning treatment of the surface of the zinc foil.
[0023] Figure 3 The present invention is a schematic diagram showing a comparison of the contact angles of the zinc foil surface with the electrolyte before laser treatment, after laser treatment, and after laser treatment combined with plasma treatment in one embodiment of the present invention; wherein (a) is a characterization diagram of the contact angle of the zinc foil surface with the electrolyte before laser treatment; (b) is a characterization diagram of the contact angle of the zinc foil surface with the electrolyte after laser treatment; and (c) is a characterization diagram of the contact angle of the zinc foil with the electrolyte after laser treatment combined with plasma treatment.
[0024] Figure 4 This is a SEM characterization image of the zinc negative electrode surface of the commercial metal zinc foil symmetrical battery in the comparative example after 100 charge and discharge cycles.
[0025] Figure 5 This is a SEM characterization image of the zinc negative electrode surface of the symmetrical battery of the modified zinc negative electrode 1 obtained in Example 1 after 100 charge and discharge cycles.
[0026] Figure 6 It is a nuclear overpotential characterization diagram of the commercial metal zinc foil symmetrical battery in the comparative example, the laser reconstructed zinc negative electrode 1 symmetrical battery in Example 1, and the modified zinc negative electrode 1 symmetrical battery. DETAILED DESCRIPTION
[0027] Example embodiments will now be described more fully with reference to the accompanying drawings. However, the example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present disclosure will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted. In addition, the drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale.
[0028] The terms "a", "an", "the", "said" and "at least one" are used to indicate the presence of one or more elements / components / etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that additional elements / components / etc. may exist in addition to the listed elements / components / etc.; the terms "first", "second", etc. are used merely as labels and are not intended to limit the quantity of their objects.
[0029] The present disclosure provides a method for preparing a modified zinc negative electrode, which can be used as a negative electrode of an aqueous zinc ion battery. Figure 1 As shown, the preparation method of the modified zinc negative electrode comprises the following steps: S10, patterning the surface of the zinc foil using an ultraviolet picosecond pulse laser to obtain a laser-reconstructed zinc negative electrode; S20, using plasma technology to perform plasma treatment on the surface of the laser reconstructed zinc negative electrode to obtain a modified zinc negative electrode.
[0030] In step S10, Figure 2 As shown in (b), the surface of the zinc foil is treated with an ultraviolet picosecond pulse laser to reduce the microcracks, scratches, folding lines and unpolished edges (such as Figure 2 The adverse effects of inherent defects such as (as shown in (a) in the figure) are eliminated, and the surface stability and uniformity of zinc foil as the negative electrode of the battery are improved. At the same time, laser treatment is used to form nano-scale grooves and protrusions on the surface of the zinc foil, so that the surface texture of the zinc negative electrode is reconstructed, thereby reducing the interface formed by the contact between the zinc negative electrode surface and the electrolyte (zinc negative electrode-electrolyte interface), which is conducive to the preferential orientation of zinc dendrite growth, thereby avoiding the growth of zinc dendrites on the surface of the zinc negative electrode. In addition, laser treatment further increases the specific surface area of the zinc negative electrode, increases the active sites on the surface of the zinc negative electrode, and provides more and uniform "anchor points" for the nucleation and deposition of zinc ions, thereby improving the electrochemical performance of aqueous zinc ion batteries.
[0031] Laser treatment is used to reconstruct the texture of the zinc negative electrode surface to form a laser reconstructed zinc negative electrode. The experiment found that when the electrolyte is dropped on the surface of the laser reconstructed zinc negative electrode, such as Figure 3As shown in (a) and (b), the contact angle after laser treatment is larger than the contact angle before laser treatment, and the contact angle increases from 94.3° to 142.7°. However, the experiment also found that when the electrolyte is added again to the position that has been in contact with the electrolyte (the area wetted by the electrolyte), the electrolyte can spread quickly, that is, the electrolyte can be quickly and evenly distributed on the surface of the laser reconstructed zinc negative electrode. Based on this, in step S20, by performing plasma treatment on the surface of the laser reconstructed zinc negative electrode, the plasma can homogenize the electric field distribution at the zinc negative electrode-electrolyte interface, and can also form polar functional groups on the surface of the zinc negative electrode, thereby improving the contact between the zinc negative electrode and the electrolyte interface, as shown in FIG. Figure 3 As shown in (c), the contact angle after laser treatment combined with plasma treatment is reduced to 53.2°.
[0032] In this embodiment, the interface layer of the zinc negative electrode (that is, the surface where the zinc negative electrode contacts the electrolyte) is reconstructed by laser treatment, and the texture on the interface layer of the zinc negative electrode is optimized, which greatly reduces the preferential orientation that is conducive to the formation of dendrite growth, optimizes the zinc negative electrode structurally, and reduces dendrite growth. At the same time, on the basis of structural optimization, the interfacial double electric layer structure formed at the zinc negative electrode-electrolyte interface is homogenized by plasma treatment, and the reconstruction of the interfacial double electric layer structure is achieved. While further inhibiting the growth of zinc dendrites and reducing side reactions, polar functional groups are introduced to increase the wettability of the interface between the electrolyte and the zinc negative electrode, and the uniformity of zinc deposition is further improved, thereby reducing the formation of dendrites. In addition, the preparation process of the modified zinc negative electrode provided in this embodiment is simple, the production cost is low, and it is conducive to application in industrial production.
[0033] Optionally, the zinc foil may be a commercial zinc foil, which is a negative electrode of an aqueous zinc ion battery in the related art. In this way, the commercial zinc foil may be directly modified to improve its performance as a zinc negative electrode without affecting the original production line, thereby reducing production costs.
[0034] In one embodiment of the present disclosure, in step S10, the patterning process is to use a laser to directly write on the surface of the zinc foil; the processing speed of the laser direct writing is 1000~2000mm / s, the straight line filling spacing is 0.005mm~0.01mm, the straight line filling angle is 0~90°, and the number of straight line fillings is 1~10 times. In this embodiment, the processing speed, straight line filling spacing, filling angle and filling number in the laser direct writing are limited. Combined with the plasma treatment process of step S20, uniform zinc deposition is achieved on the zinc negative electrode-electrolyte interface, reducing the growth of zinc dendrites during the use of the zinc negative electrode.
[0035] In this embodiment, the processing speed of laser direct writing is 1000~2000mm / s. If the processing speed is too fast, the grooves formed on the surface of the zinc foil are shallow, and the effect of modifying the surface texture of the zinc foil cannot be achieved; if the processing speed is too slow, the grooves formed on the surface of the zinc foil are deep. At the same time, slow processing will cause heat accumulation, causing ablation damage to the local part of the zinc foil, and introduce amorphous areas, and the introduction of amorphous areas will hinder the subsequent plasma chemical modification efficiency. In this way, it is necessary to adopt a suitable laser direct writing processing speed so that the deeper grooves obtained on the surface of the zinc foil can increase the unit contact area between the subsequent plasma and the surface of the zinc foil, promote the uniform growth of the oxide layer, and avoid laser direct writing on the surface of the zinc foil to form ablation, affecting the chemical modification treatment of the plasma. For example, the processing speed of laser direct writing can be 1000 mm / s, 1100 mm / s, 1200 mm / s, 1300 mm / s, 1400 mm / s, 1500 mm / s, 1600 mm / s, 1700 mm / s, 1800 mm / s, 1900 mm / s or 2000 mm / s.
[0036] In this embodiment, the straight filling spacing is 0.005mm~0.01mm. This is because the straight filling spacing of laser direct writing is related to the density of the etching pattern formed on the final zinc foil. The straight filling spacing is small (for example, less than 0.01mm), which can form a continuous groove, increase the specific surface area of the zinc foil, and then increase the active sites on the surface of the zinc foil, and also enhance the efficiency of the plasma gas grafting functional groups on the surface of the zinc foil in the subsequent plasma treatment. However, on the one hand, if the straight filling spacing is too small, the etching pattern formed is too dense, which will limit the efficiency of the subsequent plasma treatment. It is difficult for the plasma to penetrate to the bottom of the groove structure, resulting in uneven modification of the zinc negative electrode, affecting the uniform deposition of zinc, and easily leading to zinc dendrite growth. On the other hand, if the straight filling spacing is too large, an isolated structure may be formed on the surface of the zinc foil, thereby reducing the electrical performance of the zinc negative electrode in the overall structure. For example, the straight filling spacing can be 0.005mm, 0.006mm, 0.007mm, 0.008mm, 0.009mm or 0.010mm.
[0037] In this embodiment, the straight line filling angle is 0-90°. The straight line filling angle of laser direct writing is different, and the texture pattern formed on the surface of the zinc foil is different, which in turn affects the distribution of plasma in the groove during the subsequent plasma treatment process, and affects the efficiency and distribution uniformity of the grafted functional groups. For example, the straight line filling angle can be 0°, 10°, 15°, 20°, 25°, 30°, 35°, 40°, 45°, 50°, 55°, 50°, 65°, 50°, 75°, 80°, 85° or 90°.
[0038] In this embodiment, the number of linear fillings is 1 to 10 times. By performing linear fillings multiple times, a deeper groove can be obtained, and a layered structure can be formed in multiple fillings. The layered structure formed may enhance the residence time of the plasma and promote the formation of deep grafting functional groups in the groove, but too many filling times will form more cracks, introduce nuclei for zinc dendrites, and increase the possibility of zinc dendrite growth. For example, the number of linear fillings can be 1 time, 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times or 10 times.
[0039] That is to say, the laser direct writing parameters provided in the embodiments of the present invention need to cooperate with each other and work synergistically with the subsequent plasma treatment to prepare a modified zinc negative electrode with optimized surface structure and reconstructed double electric layer structure at the zinc negative electrode-electrolyte interface, thereby optimizing the zinc negative electrode from multiple aspects such as texture, double electric layer structure and chemical functional groups, thereby reducing the growth of zinc dendrites during use and reducing the occurrence of side reactions on the zinc negative electrode.
[0040] Furthermore, the processing speed of the laser direct writing is 1200-1600 mm / s, the straight line filling spacing is 0.005 mm-0.007 mm, the filling angle is 30-60°, and the filling times are 2-4 times.
[0041] Preferably, the processing speed is 1500 mm / s, the straight line filling spacing is 0.005 mm, the filling angle is 45°, and the filling times are 2 times.
[0042] In one embodiment of the present disclosure, the wavelength of the laser is 355nm; the actual power used by the laser is 1~5W, the maximum average power of the laser is 10~30W; and the pulse width is less than 15ps. That is to say, ultraviolet light with a wavelength of 355nm, also known as a cold light source, is used. During the laser direct writing process, the risk of ablation on the surface of the zinc foil is relatively small. In the laser direct writing, the actual power used by the laser is 1~5W. For example, the actual power used can be 1.0W, 1.5W, 2.0W, 2.7W, 3W, 3.6W, 4W, 4.2W, 4.8W or 5W. To ensure the accuracy of the power, the maximum average power of the laser used is 10~30W. For example, the maximum average power of the laser can be 10W, 15W, 20W, 25W or 30W. For example, when the maximum average power of the laser is 30W, the actual power used by the laser is 9% of the maximum average power of the laser, that is, 2.7W.
[0043] In one example, the pulse frequency range of the laser is 1Hz~2000kHz, the laser power stability is less than 3%, the minimum focus spot is less than or equal to 9μm, the beam quality M2 value is less than 1.2, the beam divergence angle is less than 2mrad, and the spot roundness is greater than or equal to 90%. Exemplarily, the actual use pulse frequency range of the laser is 600kHz~2000kHz. In this way, within this range, ablation of the zinc foil surface is avoided, and the processing accuracy and efficiency of laser direct writing are improved.
[0044] In one embodiment of the present disclosure, in the laser direct writing, the angle between the laser head of the laser and the surface of the zinc foil is 90°. That is, the angle between the laser beam and the surface of the zinc foil is 90°. In this way, when the laser beam is irradiated perpendicularly to the surface of the zinc foil, the laser energy can be absorbed by the zinc foil to the greatest extent, and it is beneficial to distribute the laser energy relatively evenly on the surface of the zinc foil, avoiding uneven depth or width of the processed pattern. At the same time, the laser beam is vertically emitted to the surface of the zinc foil, and the focal position of the laser beam can be more easily and accurately controlled on the surface of the zinc foil, reducing the spot distortion and improving the processing accuracy.
[0045] In one embodiment of the present disclosure, the pattern obtained by the patterning process is a stripe pattern. Exemplarily, the surface of the laser reconstructed zinc negative electrode forms an array of grooves and protrusions, perpendicular to the extension direction of the grooves, the width of the grooves is not greater than 1000nm; perpendicular to the extension direction of the protrusions, the width of the protrusions is not greater than 1000nm.
[0046] In one embodiment of the present disclosure, the pattern obtained by the patterning process is a lattice pattern. In one embodiment, a lattice pattern can be obtained by a cross-filling method. Exemplarily, the surface of the laser reconstructed zinc negative electrode forms grooves and protrusions arranged in an array, perpendicular to the extension direction of the grooves, and the width of the grooves is not greater than 1000nm. Exemplarily, the protrusions can be rectangular, rhombus, etc. Among them, the short side size of the rectangle is not greater than 1000nm; among the diagonals of the rhombus, the shorter diagonal size is not greater than 1000nm.
[0047] In one embodiment of the present disclosure, in step S20, the working gas used in the plasma treatment is at least one of helium (He), argon (Ar), oxygen (O2), nitrogen (N2), hydrogen (H2), carbon dioxide (CO2), chlorine (Cl2), xenon (Xe), and water vapor (H2O). For example, plasma treatment with oxygen can directly introduce functional polar groups such as hydroxyl (-OH) and carboxyl (-COOH) on the surface of zinc foil. These polar groups interact with the components in the electrolyte, which can not only assist in inducing the stable and uniform dissolution and deposition of zinc ions at the active sites in the patterned array, avoiding the disordered formation and growth of zinc dendrites, but also effectively reduce the decomposition of water in the electrolyte on the surface of the zinc negative electrode and the occurrence of other side reactions, thereby improving the capacity retention rate and cycle life of the aqueous zinc ion battery. For another example, argon plasma treatment can also activate the surface of zinc foil. Argon plasma can generate free radicals on the surface through physical bombardment and chemical action. These free radicals may react with oxygen in the air to indirectly form some oxygen-containing functional groups (such as hydroxyl, carboxyl and other polar groups).
[0048] Exemplarily, the gas purity of the working gas is greater than or equal to 99.99%.
[0049] In one embodiment of the present disclosure, in step S20, the plasma treatment process includes: the first stage: the gas flow rate range is 10 to 80 sccm (standard cubic centimeters per minute), the gas vacuum range is 10Pa to 30Pa, the radio frequency power is 50W to 200W, and the treatment time is ≥100s; the second stage: the gas flow rate range is 80 to 200 sccm, the gas vacuum range is 30Pa to 50Pa, the radio frequency power is 200W to 300W, and the treatment time is ≥100s. In the first stage, the surface of the laser reconstructed zinc negative electrode can be preliminarily cleaned and preliminarily modified, and the attached pollutants, oxides or residues on the surface can be further removed, and some active sites or functional groups that change the chemical properties of the surface are introduced. In the second stage, in-depth surface modification is carried out by plasma treatment, functional groups are uniformly grafted on the surface, and the interfacial double electric layer structure of the zinc negative electrode surface is reconstructed.
[0050] The disclosed embodiment also provides an aqueous zinc ion battery, wherein the negative electrode of the aqueous zinc ion battery adopts the modified zinc negative electrode obtained by the above preparation method.
[0051] The preparation method and performance of the negative electrode of the aqueous zinc ion battery disclosed in the present invention are further described below in conjunction with specific embodiments.
[0052] In the embodiments provided by the present invention, commercial zinc foil was purchased from Dongguan Kelude New Energy Technology Co., Ltd.
[0053] Comparative Example The commercial zinc foil was cut into zinc negative electrodes with a diameter of 14 mm, and the assembled aqueous zinc ion symmetric battery was a commercial metal zinc foil symmetric battery (Zn / Zn). The electrolyte was 1 mol L -1 Zinc sulfate aqueous solution, using qualitative filter paper as a separator.
[0054] Using commercial zinc foil symmetric cells (Zn / Zn), the current density was 1 mA cm -2 , capacity cutoff is 0.5 mAh cm -2 The commercial zinc foil symmetrical battery (Zn / Zn) short-circuited after 156 cycles. Figure 6 As shown, during the charge and discharge cycle test, the average core overpotential of the commercial metal zinc foil symmetric battery (Zn / Zn) was measured to be 170 mV.
[0055] Example 1 Step S10, using an ultraviolet picosecond pulse laser to pattern the surface of the zinc foil to obtain a laser reconstructed zinc negative electrode. The steps include: S101, place the commercial zinc foil on the vacuum adsorption platform at the bottom of the laser, use Advantech industrial computer control to calibrate, move the zinc foil, and then control the laser to perform laser direct writing on the surface of the zinc foil. The angle between the laser head of the laser and the surface of the zinc foil is 90°.
[0056] The parameters for laser direct writing on the surface of commercial zinc foil are as follows: the laser wavelength is 355nm, the laser direct writing area is selected as multiple circular areas with a diameter of 14mm, the maximum average power of the laser is 30W, and the actual power used is 9% of the maximum average power of the laser (that is, the actual power used is 2.7W). The pulse width is adjusted to 10ps and the pulse frequency is 700kHz; the laser power stability is 1%, the minimum focus spot is 2μm, and the spot roundness is 95%. The processing speed of laser direct writing is 1500mm / s, the straight line filling spacing is 0.005mm, the straight line filling angle is 45 degrees, and the number of straight line filling is 2 times.
[0057] S102, cutting the zinc foil after laser direct writing into a circular electrode with a diameter of 14 mm. The processing speed of laser cutting is 1000 mm / s, the laser power stability of laser cutting is 30%, the pulse frequency of laser cutting is 700 kHz, and the laser reconstructed zinc negative electrode obtained is defined as laser reconstructed zinc negative electrode 1 (L-Zn-1).
[0058] S20, plasma treatment is performed on the commercial metal zinc foil after laser etching using plasma technology. This step includes the following operations: The laser reconstructed surface of the laser reconstructed zinc negative electrode obtained in step S102 is placed in a plasma instrument with 10 electrodes placed in each layer; the working gas used is oxygen (O2) with a purity of 99.99%.
[0059] The first stage: during the plasma treatment, the gas flow rate was set at 50 sccm, the vacuum degree was 30 Pa, the RF power was 200 W, and the treatment time was 200 s. The second stage: the gas flow rate was set at 100 sccm, the vacuum degree was 40 Pa, the RF power was 300 W, and the treatment time was 200 s. The laser reconstructed zinc anode obtained by oxygen plasma treatment was defined as modified zinc anode electrode 1 (PL-Zn-1).
[0060] The laser reconstructed zinc anode 1 (L-Zn-1) electrode obtained in step S102 is assembled into an aqueous zinc ion symmetric battery and named as laser reconstructed zinc anode 1 symmetric battery (L-Zn-1 / L-Zn-1); wherein the electrolyte is 1 mol L -1 Zinc sulfate aqueous solution, using qualitative filter paper as a separator.
[0061] The modified zinc negative electrode 1 (PL-Zn-1) electrode obtained in step S20 is assembled into an aqueous zinc ion symmetric battery and named as modified zinc negative electrode 1 symmetric battery (PL-Zn-1 / PL-Zn-1); wherein the electrolyte is 1 mol L -1 Zinc sulfate aqueous solution, using qualitative filter paper as a separator.
[0062] The laser reconstructed zinc anode 1 symmetric battery (L-Zn-1 / L-Zn-1) and the modified zinc anode 1 symmetric battery (PL-Zn-1 / PL-Zn-1) were used at a current density of 1 mA cm -2 , capacity cutoff is 0.5 mAh cm -2 The charge and discharge cycle test was carried out under the conditions of . The laser reconstructed zinc negative electrode 1 symmetric battery (L-Zn-1 / L-Zn-1) short-circuited after 470 cycles; the modified zinc negative electrode 1 symmetric battery (PL-Zn-1 / PL-Zn-1) short-circuited after 661 cycles. Compared with the comparative example, the number of charge and discharge cycles of the L-Zn-1 / L-Zn-1 symmetric battery (470 times) was significantly increased compared with the number of charge and discharge cycles of the Zn / Zn symmetric battery (156 times); at the same time, the number of charge and discharge cycles of the PL-Zn-1 / PL-Zn-1 symmetric battery after oxygen plasma treatment (661 times) was further improved. It shows that the modified zinc negative electrode obtained by the preparation method provided in Example 1 greatly improves the cycle performance of the symmetric battery through laser direct writing and plasma treatment.
[0063] At the same time, the nuclear overpotential of the laser reconstructed zinc anode 1 symmetric battery (L-Zn-1 / L-Zn-1) and the modified zinc anode electrode 1 symmetric battery (PL-Zn-1 / PL-Zn-1) was detected. Figure 6 As shown, the average core overpotential of the L-Zn-1 / L-Zn-1 symmetric battery is 49 mV; the average core overpotential of the PL-Zn-1 / PL-Zn-1 symmetric battery is 35 mV. Compared with the average core overpotential (170 mV) of the Zn / Zn symmetric battery in the comparative example, the core overpotentials of the L-Zn-1 / L-Zn-1 symmetric battery and the PL-Zn-1 / PL-Zn-1 symmetric battery are significantly reduced. Among them, the average core overpotential of the PL-Zn-1 / PL-Zn-1 symmetric battery is less than the average core overpotential of the L-Zn-1 / L-Zn-1 symmetric battery. In other words, the modified zinc negative electrode obtained by laser direct writing and plasma treatment forms a symmetric battery with small energy loss during the charge and discharge process, and the battery is more efficient; at the same time, the smaller core overpotential helps the uniform growth of zinc, further reduces the formation of zinc dendrites, thereby improving the cycle stability and safety of the battery and extending the cycle life of the battery.
[0064] like Figure 4 The figure shows the SEM (Scanning Electron Microscope) diagram of the zinc negative electrode surface of the commercial metal zinc foil symmetrical battery (Zn / Zn) in the comparative example after 100 charge and discharge cycles. Figure 4 It can be seen that the zinc deposition on the surface of the zinc negative electrode is uneven, and there are obviously more zinc dendrites growing. The presence of zinc dendrites increases the nuclear overpotential, and the increase in nuclear overpotential further promotes the growth of zinc dendrites, which eventually causes the Zn / Zn symmetric battery to short-circuit after 156 cycles. Figure 5 , which is a SEM schematic diagram of the zinc negative electrode surface of the PL-Zn-1 / PL-Zn-1 symmetrical battery in Example 1 after 100 charge and discharge cycles. Figure 4 In comparison, the zinc deposition on the zinc negative electrode surface of the PL-Zn-1 / PL-Zn-1 symmetric battery is uniform, with only a small amount of zinc dendrites. Therefore, the core overpotential of the PL-Zn-1 / PL-Zn-1 symmetric battery is smaller, and the smaller core overpotential avoids the induction of dendrite formation, thereby improving the battery's cycle performance.
[0065] Example 2 The difference between Example 2 and Example 1 is that in step S101, the processing speed of laser direct writing is 1200 mm / s, the straight line filling spacing is 0.009 mm, the straight line filling angle is 60 degrees, the straight line filling number is 1, and the actual used power of the laser is 1W.
[0066] In step S20, during the plasma treatment, in the first stage, the gas flow rate during the plasma treatment is set at 60 sccm, the vacuum degree is 20 Pa, and the RF power is 100 W; in the second stage, the gas flow rate is set at 120 sccm, the vacuum degree is 50 Pa, and the RF power is 220 W. The laser reconstructed zinc anode treated with oxygen plasma prepared in this embodiment is defined as modified zinc anode 2 (PL-Zn-2).
[0067] The modified zinc negative electrode 2 (PL-Zn-2) electrode was assembled into a symmetrical battery, and the charge and discharge cycle test was carried out under the same conditions as in Example 1. The PL-Zn-2 / PL-Zn-2 symmetrical battery short-circuited after 654 cycles.
[0068] Example 3 The difference between Example 3 and Example 1 is that in step S101, the processing speed of laser direct writing is 1600 mm / s, the straight line filling spacing is 0.007 mm, the straight line filling angle is 30 degrees, the straight line filling times are 5 times, and the actual used power of the laser is 2W.
[0069] In step S20, during the plasma treatment, in the first stage, the gas flow rate during the plasma treatment is set at 40 sccm, the vacuum degree is 25 Pa, and the RF power is 50 W; in the second stage, the gas flow rate is set at 90 sccm, the vacuum degree is 45 Pa, and the RF power is 200 W. The laser reconstructed zinc anode treated with oxygen plasma prepared in this embodiment is defined as modified zinc anode 3 (PL-Zn-3).
[0070] The modified zinc negative electrode 3 (PL-Zn-3) electrode was assembled into a symmetrical battery, and the charge and discharge cycle test was carried out under the same conditions as in Example 1. The PL-Zn-3 / PL-Zn3 symmetrical battery short-circuited after 632 cycles.
[0071] Example 4 The difference between Example 4 and Example 1 is that in step S101, the processing speed of laser direct writing is 1400 mm / s, the straight line filling spacing is 0.006 mm, the straight line filling angle is 0 degrees, the straight line filling times are 4 times, and the actual used power of the laser is 3W.
[0072] In step S20, during the plasma treatment, in the first stage, the gas flow rate during the plasma treatment is set at 80 sccm, the vacuum degree is 20 Pa, and the RF power is 150 W; in the second stage, the gas flow rate is set at 130 sccm, the vacuum degree is 40 Pa, and the RF power is 280 W. The laser reconstructed zinc anode treated with oxygen plasma prepared in this embodiment is defined as modified zinc anode 4 (PL-Zn-4).
[0073] The modified zinc negative electrode 4 (PL-Zn-4) electrode was assembled into a symmetrical battery, and the charge and discharge cycle test was carried out under the same conditions as in Example 1. The PL-Zn-4 / PL-Zn-4 symmetrical battery short-circuited after 644 cycles.
[0074] Example 5 The difference between Example 5 and Example 1 is that in step S101, the processing speed of laser direct writing is 1800 mm / s, the straight line filling spacing is 0.005 mm, the straight line filling angle is 90 degrees, the straight line filling times is 10 times, and the actual used power of the laser is 5W.
[0075] In step S20, during the plasma treatment, in the first stage, the gas flow rate during the plasma treatment is set at 30 sccm, the vacuum degree is 15 Pa, and the RF power is 120 W; in the second stage, the gas flow rate is set at 80 sccm, the vacuum degree is 30 Pa, and the RF power is 250 W. The laser reconstructed zinc anode treated with oxygen plasma prepared in this embodiment is defined as modified zinc anode 5 (PL-Zn-5).
[0076] The modified zinc negative electrode 5 (PL-Zn-5) electrode was assembled into a symmetrical battery, and the charge and discharge cycle test was carried out under the same conditions as in Example 1. The PL-Zn-5 / PL-Zn-5 symmetrical battery short-circuited after 635 cycles.
[0077] Example 6 The difference between Example 6 and Example 1 is that in step S101, the processing speed of laser direct writing is 1000 mm / s, the straight line filling spacing is 0.008 mm, the straight line filling angle is 70 degrees, the straight line filling times are 8 times, and the actual power used by the laser is 4W.
[0078] In step S20, during the plasma treatment, in the first stage, the gas flow rate during the plasma treatment is set at 10 sccm, the vacuum degree is 10 Pa, and the RF power is 180 W; in the second stage, the gas flow rate is set at 180 sccm, the vacuum degree is 35 Pa, and the RF power is 270 W. The laser reconstructed zinc anode treated with oxygen plasma prepared in this embodiment is defined as modified zinc anode 6 (PL-Zn-6).
[0079] The modified zinc negative electrode 6 (PL-Zn-6) electrode was assembled into a symmetrical battery, and the charge and discharge cycle test was carried out under the same conditions as in Example 1. The PL-Zn-6 / PL-Zn-6 symmetrical battery short-circuited after 637 cycles.
[0080] Example 7 The difference between Example 7 and Example 1 is that in step S101, the processing speed of laser direct writing is 2000 mm / s, the straight line filling spacing is 0.010 mm, the straight line filling angle is 80 degrees, the straight line filling times are 6 times, and the actual power used by the laser is 3.5W.
[0081] In step S20, during the plasma treatment, in the first stage, the gas flow rate during the plasma treatment is set at 70 sccm, the vacuum degree is 30 Pa, and the RF power is 130 W; in the second stage, the gas flow rate is set at 200 sccm, the vacuum degree is 40 Pa, and the RF power is 290 W. The laser reconstructed zinc anode treated with oxygen plasma prepared in this embodiment is defined as modified zinc anode 7 (PL-Zn-7).
[0082] The modified zinc negative electrode 7 (PL-Zn-7) electrode was assembled into a symmetrical battery, and the charge and discharge cycle test was carried out under the same conditions as in Example 1. The PL-Zn-7 / PL-Zn-7 symmetrical battery short-circuited after 620 cycles.
[0083] It should be noted that, although the steps of the method for preparing a modified zinc negative electrode in the present disclosure are described in a specific order in the accompanying drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.
[0084] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modifications, uses or adaptations of the present disclosure, which follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure.
Claims
1. A method for preparing a modified zinc negative electrode, characterized in that: The following steps are involved: S10, patterning the surface of the zinc foil using an ultraviolet picosecond pulse laser to obtain a laser-reconstructed zinc negative electrode; S20, using plasma technology to perform plasma treatment on the surface of the laser reconstructed zinc negative electrode to obtain a modified zinc negative electrode.
2. The method for preparing the modified zinc negative electrode according to claim 1, characterized in that: In step S10, the patterning process is to use a laser to directly write on the surface of the zinc foil; The processing speed of the laser direct writing is 1000-2000 mm / s, the straight line filling spacing is 0.005 mm-0.01 mm, the straight line filling angle is 0-90°, and the straight line filling times is 1-10 times.
3. The method for preparing the modified zinc negative electrode according to claim 2, characterized in that: The processing speed of the laser direct writing is 1200-1600 mm / s, the straight line filling spacing is 0.005 mm-0.007 mm, the straight line filling angle is 30-60°, and the number of straight line filling times is 2-4 times.
4. The method for preparing the modified zinc negative electrode according to claim 3, characterized in that: The wavelength of the laser is 355nm; The actual power used by the laser is 1-5W, and the maximum average power of the laser is 10-30W.
5. The method for preparing the modified zinc negative electrode according to claim 3, characterized in that: In the laser direct writing, the angle between the laser head of the laser and the surface of the zinc foil is 90°.
6. The method for preparing a modified zinc negative electrode according to any one of claims 1 to 5, characterized in that: The pattern obtained by the patterning process is a stripe pattern or a dot pattern.
7. The method for preparing a modified zinc negative electrode according to claim 1, characterized in that: In step S20, the working gas used in the plasma treatment is at least one of helium, argon, oxygen, nitrogen, hydrogen, carbon dioxide, chlorine, xenon, and water vapor.
8. The method for preparing a modified zinc negative electrode according to claim 7, characterized in that: The gas purity of the working gas is greater than or equal to 99.99%.
9. The method for preparing a modified zinc negative electrode according to claim 7 or 8, characterized in that: In step S20, the plasma treatment process includes: The first stage: the gas flow rate is in the range of 10-80sccm, the gas vacuum is in the range of 10Pa-30Pa, the RF power is in the range of 50W-200W, and the processing time is ≥100s; The second stage: the gas flow rate is in the range of 80 to 200 sccm, the gas vacuum is in the range of 30 Pa to 50 Pa, the RF power is in the range of 200 W to 300 W, and the processing time is ≥100 s.
10. An aqueous zinc ion battery, characterized in that: The negative electrode of the aqueous zinc ion battery is a modified zinc negative electrode prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method and application of aqueous zinc ion battery negative electrode material
CN117317118A
Electrode with pit patterns for secondary battery, and preparation method and application of electrode
CN106784611A
Aqueous zinc ion battery negative electrode
CN115360317A
Metal negative electrode for secondary battery and method for manufacturing same
WO2024253053A1
KR20240156135A
Cited By
Composite passivation layer, zinc metal negative electrode, zinc metal negative electrode modification method and application
CN120400821A